Teaching reading comprehension on narrative text by using short story: A case on teaching method - Sinamo, David Suranta; Herman, Herman; Marpaung, Tiarma Intan (Institute of Education and Social Research, 2023)
The main goal of this research is to know the effect of short story as a media to the students’ ability in reading comprehension. Short story can help the students at Grade Eight in SMP Negeri 9 Pematangsiantar to improve their ability in Reading Comprehension because the students had low motivation in reading. This research applied quantitative method. The population of this research at grade eight of SMP Negeri 9 Pematangsiantar. The subject of this research is VIII-1 as experimental class consist of 30 students. and VIII-2 as the control class consist of 30 students. To analyze data, researcher used SPSS version 24, by conducting descriptive analysis, normality test, Wilcoxon test, Homogeneity test and Mann Whitney test. The results of data analysis using Mann Whitney test it is found that the Assymp value. Sig (2-tailed) on the Mann Whitney test is 0.000 < 0.05 Ha is accepted and H0 is rejected. According to the aforementiond data, it can be concluded that using short story as a media, has a more significant impact than the class that do not use short story to the students’ ability in reading comprehension on recount text at grade eight in SMP Negeri 9 Pematang Siantar. The result is the mean score of post-tests in experimental class is 88,50 and, in the control, class the score of post-test is 45,00. Based on the finding of this research, the researcher concludes that the alternative hypothesis (Ha) is accepted and null hypothesis (H0) is rejected.